MANAJEMEN ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN FLOUR ALBUS PATOLOGIS PADA NY’’A’’ DI KLINIK WIRAHUSADA MEDICAL CENTER MAKASSAR TANGGAL 01 OKTOBER – 30 NOVEMBER 2021 - Jusmawati; Saleha, Sitti; Setiawati, Dewi (Jurnal Midwifery, 2022)
Introduction Vaginal discharge is a condition that is often experienced by women throughout the phase of their life commencing from adolescence, reproduction age, and cycle characterized by odorless and clear fluid. The normal vaginal discharge does not also couse any itching and pain. However, abnormal vaginal discharge occurs because of infection from various microorganisms, including bacteria, fungi and parasites. The major purpose of this study was to conduct the midwifery care management on a pregnant patient with the case of pathological flour albus. This research was conducted at Wirahusada Medical Center of Makassar based on the 7stages of varney Management approach and SOAP documentation procedure. The findings of this research indicated that the treatment given to Mrs ‘’A’’ was considered to be good in which the amoung of vaginal discharge experienced by the patient reduced, and the itching and pain could be overcome. The treatment and monitoring were conducted for 5 times, the patient was suggested to maintaint her vaginal moisture, reduce stress, and decrease any tireless activities. At the time of examination, the condition of the fetus wa in good condition where the blood pressure of the patient was 100/70 mmHg. The patient also had no complaints or complication from her pathological flour albus. Finally, based on the research data analysis, this research could be concluded that the problem found on Mrs ‘’A’’with pathological flour albus at Wirahusada Medical Center of Makassar was well resolved. The general condition of the patient was good, and the fetus was also considered to be in a good condition. The patient showed composmentis consciousness, and her vital signs were within normal limits moreover, the results of the examination showed no signs of infection.